A systematic review of the early dialogue frameworks used within health technology assessment and their actual adoption from HTA agencies - Ibargoyen-Roteta, Nora; Galnares-Cordero, Lorea; Benguria-Arrate, Gaizka; Chacón-Acevedo, Kelly Rocío; Gutiérrez-Sepulveda, María Paula; Low-Padilla, Eduardo; De La Hoz-Siegler, Ilich Herbert; Guevara-Pérez, Claudia Isabel; Pozo-Pérez, Ángel del; Suárez, Marta; Dauben, Hans Peter; Otte, Maximilian; et al. (Frontiers in Public Health, 2022)
Introduction: Early advice in the framework of the development of health technologies allows manufacturers to plan more accurately the production and transfer of technologies to health care systems. The aim of this article is to describe this type of frameworks used within HTA and their current level of adoption from HTA Agencies. Material and Methods: We performed a systematic literature review in Pubmed, Embase, Scopus, and WoS, including all references published in Spanish and English. Websites of several HTA organizations and Google were also searched. The search was last updated in March 2022.We extracted all the available information about the organizations involved, services offered, type of technologies, description of the advice services, the stakeholders involved, fees, output, and impact. Results: 541 articles were screened and finally twenty-five meeting the eligibility criteria were chosen. Seven of them were reviews that described two or more HTA organizations. Ten studies were focused on the advice offered by individual organizations, and eight described the EMA and EUNETHA parallel or joint advice. We found variability in the technology assessed, services offered, stage in the development cycle, and advice costs. Conclusions: Early and scientific advice would help manufacturers focus their product development on what is needed for the management of a specific disease/s. Unfortunately, this review has not identified many examples or services for medical devices and diagnostics. However, this finding is very relevant; as a matter of fact, developing “Medtech” technologies is more challenging because it is less regulated and structured than pharmaceuticals.